ISOLATION AND IDENTIFICATION OF PROTEINS FROM POTATO LEAVES - Szajko, Katarzyna (Plant Breeding and Seed Science, 2017)
Potato leaves are a very convenient material to compare the differences in potato proteomes. Prote-ins isolation depends on the type of analysis. The method of isolation of proteins from potato leaves, 2D electrophoresis and liquid chromatography–tandem mass spectrometry (LC-MS/MS) were descri-bed in detail.